KOMUNIKASI RITUAL DALAM HARMONISASI PERILAKU BERAGAMA - I Gusti Ayu Ratna Pramesti Dasih; I Gusti Ayu Diah Prameswara Padawati Indraswari (Widya Duta: Jurnal Ilmiah Ilmu Sosial Budaya, 2022)
Ritual communication is carried out by communities that carry out ceremonies and cultural tradition throughout their years and live, to express words or display certain symbolic behaviors. Message in ritual communication are usually hidden and confusing, sometimes having multiple meanings, depending on tradition and culture. The belief system, religion, and worship greatly affect the perception of messages in ritual communication. The process of ritual communication occurs due to supporting factors such as liturgical rites, belief systems, and worship systems. Two-way communication process is applied to support religious, social and ethical-based ritual communication activities. Social interaction is built to establish communication so that it has implications for strengthening religious attitudes, social communicative actions, and cultural values.